As it is Now [Director: Lesley Kaiser. Animation and Editing : Logan Austin] - Kaiser, L; Austin, L (The Centre for Contemporary Art, Thessaloniki State Museum of Contemporary Art, 2011)
This animation of daily photos (by Lesley Kaiser) of a blossom tree over a period of one year tracks the changing seasons in the microcosm of a Ponsonby garden, and responds to the fact that we are biological beings (and that any encounter with a work of art is a biological encounter). This work looks at digital aesthetics in nature within the wider context of cognitive science, evocriticism, poetry, and from an art practitioner’s perspective. Created in an era of climate change, the work is set against a background of a dying native cabbage tree, and nostalgically captures for the future the delight that springtime may bring, as well the sadness inherent in things (the Japanese concept of mono no aware). Technical aspects of animation: Logan Austin
Keywords: Animation; Visual arts; Blossom; Poetry; Evocritism